2010
DOI: 10.1165/rcmb.2009-0053oc
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Epithelial Sodium Channel δ-Subunit in Human Nasal Epithelium

Abstract: The epithelial sodium channel (ENaC) mediates the first step in Na+ reabsorption in epithelial cells such as kidney, colon, and airways and may consist of four homologous subunits (alpha, beta, gamma, delta). Predominantly, the alpha-subunit is expressed in these epithelia, and it usually forms functional channels with the beta- and gamma-subunits. The delta-subunit was first found in human brain and kidney, but the expression was also detected in human cell lines of lung, pancreatic, and colonic origin. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…In our hands, Evans blue reduced currents across both NCI-H441 and ATI-like cell monolayers, which was consistent with previous observations in oocytes [48] and HNE cells [3], but exhibited concentration-dependent stimulatory effects on the I SC in Calu-3 cells.…”
Section: Effects Of Pharmacological Modulators Of δ-Enac Function On supporting
confidence: 92%
See 2 more Smart Citations
“…In our hands, Evans blue reduced currents across both NCI-H441 and ATI-like cell monolayers, which was consistent with previous observations in oocytes [48] and HNE cells [3], but exhibited concentration-dependent stimulatory effects on the I SC in Calu-3 cells.…”
Section: Effects Of Pharmacological Modulators Of δ-Enac Function On supporting
confidence: 92%
“…Only a single publication, however, reported the use of these compounds as modulators of δ-ENaC function in an organotypic in vitro model, i.e. in human nasal epithelial (HNE) cells [3]. No functional evidence has yet been provided for other respiratory epithelial cell types, in particular NCI-H441 cells, for which δ-ENaC expression has been reported repeatedly [27, 37, 38].…”
Section: Effects Of Pharmacological Modulators Of δ-Enac Function On mentioning
confidence: 99%
See 1 more Smart Citation
“…have been functionally detected in human nasal epithelial cells (36). We previously found that CPT-cGMP activated dabg ENaC in oocytes (26).…”
Section: Cpt-cgmp Stimulates Abg But Not Dbg Enacmentioning
confidence: 95%
“…This is supported by a very recent finding that ␦ ENaC channels contributed to ϳ50% of amiloride-sensitive salt transport across primary human nasal epithelial cells (3). We and others (3,29,37) have recently shown that an additional ENaC subunit (termed ␦ ENaC) may account for diverse observations in the biophysical properties of native epithelial Na ϩ channels. Biophysical and pharmacological studies such as these in Xenopus oocytes have shown that heteromultimeric ␦␤␥ ENaC channels exhibited high selectivity for Na ϩ over Li ϩ ions, less amiloride sensitivity than ␣␤␥ ENaC (25, 36, 44), and were regulated by changes in extracellular pH (24,36,53).…”
mentioning
confidence: 99%